Targeted Next-Generation Sequencing of Circulating Tumor DNA, Bone Marrow, and Peripheral Blood Mononuclear Cells in Pediatric AML - Ruan, Min; Liu, Lipeng; Qi, Benquan; Chen, Xiaoyan; Chang, Lixian; Zhang, Aoli; Liu, Fang; Wang, Shuchun; Liu, Xiaoming; Chen, Xiaojuan; Zhang, Li; Guo, Ye; et al. (Frontiers in Oncology, 2021)
Background The aim of the study was to validate the diagnostic role of circulating tumor DNA (ctDNA) in genetics aberration on the basis of next-generation sequencing (NGS) in pediatric acute myeloid leukemia (AML). Methods Bone marrow (BM) and peripheral blood (PB) were collected from 20 AML children at the time of initial diagnosis, and a ctDNA sample was isolated from PB. Detection of mutation was performed on ctDNA, BM, and peripheral blood mononuclear cell (PBMC) by NGS based on a 185-gene panel. Results Among 185 genes sequenced by the NGS platform, a total of 82 abnormal genes were identified in 20 patients. Among them, 61 genes (74.39%) were detected in ctDNA, PBMC, and BM samples, while 11 (13.41%) genes were found only in ctDNA and 4 (4.88%) were detected only in the BM sample, and 2 (2.44%) were detected only in PBMC. A total of 239 mutations were detected in three samples, while 209 in ctDNA, 180 in bone marrow, and 184 in PBMC. One hundred sixty-four mutations in ctDNA were shared by matched BM samples, and the median variant allelic frequency (VAF) of these mutations was 41.34% (range, 0.55% to 99.96%) and 44.36% (range, 0.56% to 99.98%) in bone marrow and ctDNA. It was found that 65.79% (75/114) of mutations with clinical significance were detected in three samples, with 9 mutations detected both in ctDNA and BM, and 2 mutations detected both in PBMC and BM. The consistency of mutations with clinical significance between ctDNA and BM was 77.06% (84/109). Among the 84 mutations with clinical significance detected in both sources, the concordance of VAF assessment by both methods was high (R2 = 0.895). Conclusion This study demonstrates that ctDNA was a reliable sample in pediatric AML and can be used for mutation detection. Consistency analysis showed that ctDNA can mirror the genomic information from BM. In addition, a subset of mutations was exclusively detected in ctDNA. These data support the fact that monitoring ctDNA with next-generation sequencing-based assays can provide more information about gene mutations to guide precision treatment in pediatric AML.